Analyzing Quality of Human Resources and Risk-Taking in the Performance of Creative Industry MSMEs in Tabanan Regency - Suriani, Ketut; Merta, I; Ardiansyah, Wisnu (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Bali possesses significant potential for production and trade within the Micro, Small, and Medium Enterprises (MSMEs) industrial sector, in addition to its tourism. This study aims to analyze the impact of quality of human resource factors and risk-taking behavior on the performance of MSMEs in the creative industries of the Tabanan district, using the resource-based view model concept. The research employs a quantitative method, including a questionnaire, with a sample of 54 MSMEs. Data processing is conducted using SPSS version 24, and three hypotheses are tested. The research findings indicate that the quality of human resources significantly enhance creative industry performance, and the risk-taking also contributes positively to creative industry performance. Furthermore, the quality of human resources significantly influence risk-taking. These results underscore the substantial and dominant implications of both the quality of human resources and risk-taking variables on the performance of creative industry MSMEs. ABSTRAK Bali memiliki potensi yang signifikan untuk produksi dan perdagangan dalam sektor industri Usaha Mikro, Kecil, dan Menengah (UMKM), selain dari sektor pariwisatanya. Penelitian ini bertujuan untuk menganalisis dampak faktor sumber daya manusia dan perilaku mengambil risiko terhadap kinerja UMKM di industri kreatif kabupaten Tabanan, dengan menggunakan konsep model berbasis sumber daya. Penelitian ini menggunakan metode kuantitatif, termasuk kuesioner, dengan sampel sebanyak 54 UMKM. Pengolahan data dilakukan menggunakan SPSS versi 24, dan tiga hipotesis diuji. Temuan penelitian menunjukkan bahwa sumber daya manusia secara signifikan meningkatkan kinerja industri kreatif, dan pengambilan risiko juga memberikan kontribusi positif terhadap kinerja industri kreatif. Selain itu, sumber daya manusia secara signifikan memengaruhi pengambilan risiko. Hasil ini menekankan implikasi yang signifikan dan dominan dari kedua variabel sumber daya manusia dan pengambilan risiko terhadap kinerja UMKM di industri kreatif. Kata kunci: Sumber Daya Manusia, Pengambilan Risiko, Kinerja UMKM, Industri Kreatif, Bali